Swedish election study 1991 - Holmberg, Sören; Gilljam, Mikael; Statistics Sweden (University of Gothenburg, 1993)
Since 1956 an election study has been carried out in connection with a Swedish general election. This study is accordingly number twelve of the collection. Many of the questions are replications of questions asked in one or several of the previous surveys, but there are also a number of questions not asked before. In this survey the respondents had to give their opinion on the major tax reform completed in this year. They also had to indicate what they considered most important to fight against, unemployment or inflation, and their opinion on the preferences of the political parties. In view of the deteriorating economy the respondents had to give their opinion on the cause of the economic problems in Sweden, and how the situation would have been if there had been a bourgeois government. The respondents also had to indicate if they had been affected by the tightening labour market. A number of questions dealt with the European Community and a possible Swedish membership.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Detta är den tolfte riksomfattande studien i serien undersökningar kring partival, valdeltagande och opinionsbildning inom den svenska valmanskåren i samband med ett riksdagsval. Undersökningen ingår som steg två i panelen 1988-1991 och som steg ett i panelen 1991-1994.

Ett stort antal av frågorna har ställts i en eller flera tidigare valundersökningar. Nya frågeställningar i denna undersökning tar upp inställningen till 1991 års skattereform samt vad man anser viktigast att bekämpa, arbetslöshet eller inflation. Respondenterna fick även ange vad man trodde var den viktigaste orsaken till Sveriges försämrade ekonomi och hur man trodde situationen skulle ha varit med en borgerlig regering samt om man själv blivit drabbad av det försämrade läget på arbetsmarknaden. Ett antal frågor berörde Europeiska Gemenskapen och ett möjligt svenskt medlemskap.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1991
VU91
Keywords: elections; val; mass media; massmedia; occupations; yrken; politics; politik; public sector; offentlig sektor; social mobility; social rörlighet; international relations; internationella relationer; employment; anställning; energy; energi; environment; miljö; economics; ekonomi; voting; röstning; parliamentary elections; riksdagsval; political interest; politiskt intresse; taxation; beskattning; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; party politics; partipolitik; political parties; politiska partier; social policy; politik (policy); political leaders; politiska ledare; election campaigns; valkampanjer; electoral issues; valfrågor; trade unions; fackföreningar; organizations; organisationer; trust in government; förtroende för regeringen; minority groups; minoritetsgrupp; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap